Structural and biochemical characterization of the protease domain of the mosaic botulinum neurotoxin type HA. Issue 4 (23rd April 2018) - Lam, Kwok-ho; Sikorra, Stefan; Weisemann, Jasmin; Maatsch, Hannah; Perry, Kay; Rummel, Andreas; Binz, Thomas; Jin, Rongsheng
Abstract: The extreme toxicity of botulinum neurotoxins (BoNTs) relies on their specific cleavage of SNARE proteins, which eventually leads to muscle paralysis. One newly identified mosaic toxin, BoNT/HA (aka H or FA), cleaves VAMP-2 at a unique position between residues L54 and E55, but the molecular basis underlying VAMP-2 recognition of BoNT/HA remains poorly characterized. Here, we report a ∼2.09 Å resolution crystal structure of the light chain protease domain of BoNT/HA (LC/HA). Structural comparison between LC/HA and LC of BoNT/F1 (LC/F1) reveals distinctive hydrophobic and electrostatic features near the active sites, which may explain their different VAMP-2 cleavage sites. When compared to BoNT/F5 that cleaves VAMP-2 at the same site as BoNT/HA, LC/HA displays higher affinity for VAMP-2, which could be caused by their different surface charge properties surrounding a VAMP-2 exosite-binding cleft. Furthermore, systematic mutagenesis studies on VAMP-2 and structural modeling demonstrate that residues R47 to K59 spanning the cleavage site in VAMP-2 may adopt a novel extended conformation when interacting with LC/HA and LC/F5. Taken together, our structure provides new insights into substrate recognition of BoNT/HA and paves the way for rational design of small molecule or peptide inhibitors against LC/HA. Abstract : Crystal structure of the protease domain of the mosaic botulinum neurotoxin type HA.